THE DRIVERS TO DEVELOPMENT OF INNOVATIVE TERRITORIAL CLUSTERS - E. Karkhanova (Вестник университета)
This article explores drivers of innovative territorial clusters .The approaches of such scientists as M Porter, J. Bagvel, J. J. Cortright, A Bosquet, S. Mothe were studied. The paper outline that existing academic literature offers a static view of cluster drivers that does not adequately capture the effect of complex interrelationships which exist between cluster drivers. The author suggested own classification of drivers of innovative territorial clusters. The author singeled such drivers as global competition, government, exchange of risks and information on expenses, supply chain changes, anticipation of increased workload, project management.